Perancangan Warning System Berbasis SMS Gateway Pada Pajak Kendaraan Bermotor Di Samsat Kota Padang - Rinaldi Dwi Putra Mooduto; irman Surya; Rasyidah Mustika (Jurusan Akuntansi Politeknik Negeri Padang, 2017)
This study aims to design, design, and test information service ased on SMS gateway so that it can help the SAMSAT Padang in improving services on motor vehicle tax collection process. The design of the system to be built, consist of table design, input design, and output design. Tests conducted using test data. The result of this research is the creation of an SMS gateway information system prototype that can provide information to SAMSAT Padang and owner of motor vehicle concerning their vehicle tax obligation.